Thanksgiving all year round : a memoir - Shapiro, Gavriel (Brighton, MA, USA : Academic Studies Press, 2016)
The book describes the author's eventful life, which spans over seventy years, in three different countries and on as many continents.
Pages:1 to 25; Pages:26 to 50; Pages:51 to 75; Pages:76 to 100; Pages:101 to 125; Pages:126 to 150; Pages:151 to 175; Pages:176 to 200; Pages:201 to 225; Pages:226 to 250; Pages:251 to 275; Pages:276 to 293.
Includes bibliographical references and index.
Print version record.
Keywords: Shapiro, Gavriel; Jews -- Soviet Union -- Social conditions -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Social Scientists & Psychologists; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Minority Studies; Electronic books